Pengaruh Penggunaan Media Sosial, Gaya Hidup, dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa di Kota Surakarta - Dewi Wulandari; R. Taufiq Nur Muftiyanto; Agus Suyatno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The consumer behavior of university students is an intriguing phenomenon to explore given the dominant influence of social media and evolving lifestyles among students. This study aims to investigate the relationship between social media usage, lifestyle, and financial literacy on the consumer behavior of students in Surakarta City. The research employed a quantitative approach, collecting data from 97 active student respondents using social media from several universities in Surakarta City. A structured questionnaire was used to gather data on variables such as social media usage, lifestyle, financial literacy, and student consumer behavior.The data analysis results indicate a significant positive correlation between social media usage and student consumer behavior. Additionally, a consumptive lifestyle also positively influences student consumer behavior. However, financial literacy does not show a positive influence on student consumer behavior in Surakarta City. These findings underscore the importance of financial literacy education among students as a preventive measure against the negative effects of social media usage and consumptive lifestyles.The implications of this study can serve as a basis for developing educational programs and policies aimed at enhancing awareness and financial skills among students.